La refutabilidad del sistema de epiciclos y deferentes de Ptolomeo - Carman, Christian Carlos (2011)
To assert that the ancient planetary theory proposed by Ptolemy was irrefutable –at least until the telescope discovery- is a bit of a cliché. The aim of this paper is to analyze in what sense it could be said that the epicycle and deferent model proposed by Ptolemy to explain the planetary movement is irrefutable and in what sense it is not. To do this, we will use the conceptual framework developed by the Struturalist Conception, and in particular, the Moulines’ analysis of the "guiding principles".